Produção privada e provisão da habitação para os pobres: estrutura, mudança e impacto na Região Metropolitana de Belo Horizonte - Paola Rogedo Campos (2014)
From the intertwined relationship between private production, urban land and government regulatory action to provide housing for the poorest, this thesis discusses the role of developers and construction companies and the impact of its recent housing production in the urban concentration of Metropolitan Belo Horizonte, based on the public program Minha Casa Minha Vida. It is thus a primary data collection and analysis of the literature that seeks to understand to what extend this relationship is redefined, the extend to which new business strategies surprise and the extent to which old problems related to housig production, meeting the demand of the poorest and territorial organization of cities persist. In this regard, the reference to housing policy since the days of the Banco Nacional da Habitação and the strong bond that private sector have with the state seem to be inevitable for the analysis of social and spatial impacts resulting from implementation of a new public program of enormous proportions, launched in the midst of a period of actual growth and expasion of the real estate, but impacted by the international economic crisis. This hybrid environment leads to the discussion on the internal institutional disatirculation, as the Minha Casa Minha Vida appears to have been prepared on the sidelines of the formulation of urban policy precepts, and at the same time, formatted based on programs implemented in very context of the federal government. Therefore, there arises the question raised here: amidst disharmonies, continuities, regressions and progress in brasilian housing policy, to what extend and under what conditions the developers and construction companies provide, currently, access to housing for the poorest?